Efeito de tratamentos térmicos na resistencia à tribocorrosão da liga Inconel 718 - Januario, Marcela Eduarda (2024)
The nickel superalloy Inconel 718 stands out in the offshore oil and gas industry for its remarkable corrosion resistance. However, its low hardness and wear resistance limit its application in its as-supplied state, which is why solution hardening and aging have been widely investigated as an alternative to improve these properties. However, it is necessary to verify whether the hardening promoted by these treatments interferes with the alloy’s tribocorrosion resistance and the synergistic effect of corrosion and wear phenomena. Therefore, this work investigated the effect of five heat treatment conditions on the Inconel 718 alloy, evaluating its performance through tribocorrosion, pure wear and pure corrosion tests conducted in 3.56% (w/w) sodium chloride medium with subsequent characterization by instrumented hardness, optical interferometry and scanning electron microscopy. From the pure corrosion tests, it was found that there was no significant impact on the corrosion resistance of the material even after hardening resulting from the increase in heat treatment stages and times. Regarding wear, although aging promoted an improvement in the rate of material loss in relation to the sample that had only been solubilized, pure wear was still responsible for the largest fraction of material loss among the phenomena observed, with abrasion being the majority type, with adhesion also contributing significantly. Finally, the synergistic effect observed in longer treatments resulted in higher values of material loss rate, with wear being more influenced by corrosion.